How Diversification Moderates the Impact of Intellectual Capital, Capital Structure, and Operating Costs on Financial Performance in the IDX Food and Beverage Sector (2017-2022) - Husnaini, Husnaini; Widhiastuti, Susanti (MANAZHIM, 2025)
This study explores how the Diversification Strategy mediates financial outcomes associated with Intellectual Capital, Capital Structure, and Operational Costs. The population comprised food and beverage firms listed on the Indonesia Stock Exchange from 2017 to 2022. Samples were selected via purposive sampling from fifteen different companies. Data were sourced secondarily from the IDX Website. Moderate Regression Analysis (M.R.A.) was conducted using SmartPLS software version 3.0, with a significance level set at α (alpha) 0.05 in this research. It was demonstrated that Intellectual Capital and Capital Structure impact financial performance. Conversely, neither Operational Costs nor Diversification Strategy influence the company's bottom line. According to the study's findings, aspects of financial performance related to intellectual capital, capital structure, and operational expenses are unaffected by the diversification approach.